Investigating the Transfer of Argumentation Skills through Engagement in an Online Learning Platform - Fayyaz Ahmad Faize, Fazal Ur Rahman (PJDOL, 2023)
The learning and instruction process in Pakistan is geared around teacher-centered activities. This research aimed at involving high school students in an interactive online learning experience and to explore the acquiring of scientific argumentation skills through this online engagement. The secondary objective of the study was to investigate the transfer of argumentation skills learned through online learning to its application in other subjects.